Abnormal modification of histone acetylation involved in depression-like behaviors of rats induced by chronically unpredicted stress. Issue 16 (8th November 2017) - Li, Hai-Yan; Jiang, Qing-Song; Fu, Xiao-Yan; Jiang, Xin-Hui; Zhou, Qi-Xin; Qiu, Hong-Mei
Abstract : Depression is a complex multifactorial mental disorder. Its etiology involves many factors such as social environments, genetics, and psychology. Recent studies have shown that epigenetic modification may be associated with depression. Histone acetylation is one of the main mechanisms of epigenetic modification and plays an important role in genetic expression. In this study, we investigated the role of histone acetylation in the depression-like behaviors of rats undergoing chronically unpredicted stress (CUS) by detecting the mRNA and protein expression of histone deacetylase 5, cAMP-response element-binding protein, and the level of histone acetylated modification of H3K14, H3K23, and H4K16 in the prefrontal cortex and hippocampus of the rats. The results showed that significantly increasing depression-like behaviors were observed with a decreasing histone acetylated modification level, especially on acytelated-H3K14, acytelated-H3K23, and acytelated-H4K16, upregulating histone deacetylase 5 expression and downregulating cAMP-response element-binding protein expression in CUS rats, compared with control rats. The results indicate that the decrease in the histone acetylation modification level may be partly involved in the mechanism of depression-like behaviors of rats induced by CUS.